Multivariate statistical analysis of the essential oils of five beilschmiedia species from Peninsular Malaysia - Wan Mohd Nuzul Hakimi Wan Salleh (Tanjung Malim, 2021)
Multivariate statistical analysis of the essential oils of five beilschmiedia species from Peninsular Malaysia by Wan Mohd Nuzul Hakimi Wan Salleh